2004
DOI: 10.1377/hlthaff.23.6.210
|View full text |Cite
|
Sign up to set email alerts
|

Patterns Of Individual Health Insurance Coverage, 1996–2000

Abstract: Information about patterns of individual health insurance coverage is limited.Knowledge gaps include the extent to which individual insurance provides transitional versus long-term coverage, and participants' insurance status before and after being covered by an individual plan. In this study we use data from the 1996-2000 Survey of Income and Program Participation (SIPP) to examine how long the individually insured maintain their coverage; sources of coverage before and after enrolling in an individual health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…Recent studies have found that the nongroup market is small, volatile, and subject to potential market failures. 18,19 Persons with nongroup plans are nearly 3 times as likely to bear high total burdens as individuals in any other insurance category, including the uninsured. …”
Section: Commentmentioning
confidence: 99%
“…Recent studies have found that the nongroup market is small, volatile, and subject to potential market failures. 18,19 Persons with nongroup plans are nearly 3 times as likely to bear high total burdens as individuals in any other insurance category, including the uninsured. …”
Section: Commentmentioning
confidence: 99%
“…However, the conventional view is that the individual market primarily serves to bridge short-term gaps in group coverage instead of providing long-term, continuous coverage. 16 Our study of the California market, in contrast, suggests that the market is an important source of long-term coverage for a sizable fraction of those who purchase it. About 60 percent of new coverage episodes continue more than one year, and more than 30 percent continue for more than three years (Exhibit 1).…”
Section: Study Resultsmentioning
confidence: 86%
“…3 They looked only at people who began with individual insurance and at those who terminated spells of this type of insurance for a wide variety of alternatives (group insurance, public insurance, and becoming uninsured), not at those who persisted. In contrast, we compared people who started with group insurance as well as individual insurance.…”
Section: Study Data and Methodsmentioning
confidence: 99%